2021
DOI: 10.3892/or.2021.7972
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet storage promotes murine pancreatic tumor growth

Abstract: Hypoxia Inducible Lipid Droplet Associated (HILPDA) is frequently overexpressed in tumors and promotes neutral lipid storage. The impact of Hilpda on pancreatic ductal adenocarcinoma (PDAC) tumor growth is not known. In order to evaluate Hilpda-dependent lipid storage mechanisms, expression of Hilpda in murine pancreatic cells (KPC) was genetically manipulated. Lipid droplet (LD) abundance and triglyceride content in vitro were measured, and model tumor growth in nu/nu mice was determined. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Notably, ATGL levels decrease with PEDF knockdown, suggesting that ATGL in pancreatic cancer may not have the same pro-metastatic ability as in breast cancer. Similarly, in another PDAC mouse model, inhibition of ATGL did not alter the difference in triglyceride abundance between Hilpda wild-type and knockdown cells ( 32 ). Therefore, in PDAC, ATGL may not be a critical factor in tumor proliferation and metastasis but might be a key factor in tumor formation.…”
Section: Different Roles Of Atgl In Tumorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, ATGL levels decrease with PEDF knockdown, suggesting that ATGL in pancreatic cancer may not have the same pro-metastatic ability as in breast cancer. Similarly, in another PDAC mouse model, inhibition of ATGL did not alter the difference in triglyceride abundance between Hilpda wild-type and knockdown cells ( 32 ). Therefore, in PDAC, ATGL may not be a critical factor in tumor proliferation and metastasis but might be a key factor in tumor formation.…”
Section: Different Roles Of Atgl In Tumorsmentioning
confidence: 95%
“…Similarly, in pancreatic cancer cells, the bioinformatic analysis also revealed elevated expression of hypoxic lipid droplet-associated proteins ( 10 ). Moreover, in pancreatic ductal adenocarcinoma (PDAC) mouse model, HIG-2 was also found to increase the accumulation of LDs in cancer cells and promote the growth of cancer cells ( 32 ). Functionally, HIG-2 regulates fat storage in response to insufficient oxygen supply outside the cell or excess fatty acid content in the cell.…”
Section: Regulation Of Atgl In Cancermentioning
confidence: 99%
“…Based on the double‐edged roles of LDs in multiple cancers, the influence of LDs on tumor growth and metastasis needs to be spelled out in the context of PC. Previous data showed that LDs were drastically increased in PC [ 57 ], and that LD accumulation was correlated with the tumor growth and aggressiveness [ 220 , 221 ]. Another study showed that the number of LDs in pancreatic CSCs was higher than that in non‐CSCs, and the peroxisome proliferator‐activated receptor α (PPARα) activation, which is considered a downstream factor of LD‐derived signaling, was observed in CSCs, implicating that LD‐PPARα axis is possibly involved in the maintenance of CSC properties [ 222 ].…”
Section: Alterations Of Lipid Metabolism In Pcmentioning
confidence: 99%